2008
DOI: 10.1007/s00018-008-8371-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the multiple functions of protein C inhibitor

Abstract: Protein C inhibitor (PCI) is a widely distributed, multifunctional member of the serpin family of protease inhibitors, and has been implicated in several physiological processes and disease states. Its inhibitory activity and specificity are regulated by binding to cofactors such as heparin, thrombomodulin and phospholipids, and it also appears to have non-inhibitory functions related to hormone and lipid binding. Just how the highly conserved serpin architecture can support the multiple diverse functions of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Inhibitory serpins have very diverse functions depending on their specificity, but their importance is highlighted by the serpinopathies—diseases caused by serpin dysfunction or deficiency (Belorgey et al, 2007). Emphysema, cirrhosis, angioedema, hypertension, and even familial dementia are caused at least in part by serpin dysfunction (Kim et al, 1995; Davis et al, 1999; Ekeowa et al, 2009; Huntington and Li, 2009; Lomas et al, 2016). …”
Section: Serine Protease Inhibitors In Ticksmentioning
confidence: 99%
“…Inhibitory serpins have very diverse functions depending on their specificity, but their importance is highlighted by the serpinopathies—diseases caused by serpin dysfunction or deficiency (Belorgey et al, 2007). Emphysema, cirrhosis, angioedema, hypertension, and even familial dementia are caused at least in part by serpin dysfunction (Kim et al, 1995; Davis et al, 1999; Ekeowa et al, 2009; Huntington and Li, 2009; Lomas et al, 2016). …”
Section: Serine Protease Inhibitors In Ticksmentioning
confidence: 99%
“…6D demonstrates that the curves were superimposed, indicating no change in the affinity. It is concluded that Alboserpin belongs to the subfamily of serpins, such as AT (40), heparin cofactor II (43), protease nexin I (44), protein Z inhibitor (45), PAI-1 (46), and PCI (47), that reportedly binds heparin and other glyco- saminoglycans. However, heparin does not operate as a bridge for Alboserpin to interact with proteinases.…”
Section: Specifiticy Of Alboserpin-mentioning
confidence: 99%
“…However, PCI was later demonstrated to interact with oxidized PE or oxidized PS but not with PC (47,51). Therefore, binding of Alboserpin to phospholipids vesicles in solution was investigated.…”
Section: Kinetics and Stoichiometry Of Alboserpin-fxa Interactions-mentioning
confidence: 99%
“…[12][13][14][15][16] We identified a putative tumor-suppressor gene SerpinA5, also referred to as plasminogen activator inhibitor-3 (PAI-3) or protein C inhibitor (PCI), as being differentially expressed between serous borderline tumors and carcinomas. 16 SerpinA5 is a member of the serine protease inhibitor superfamily 17 that inactivates a variety of plasma proteases, including urokinase-type plasminogen activator (uPA), anticoagulant serine proteases, blood coagulation factors and fibrinolytic enzymes. 18 The presence of SerpinA5 in serous borderline tumors indicates that despite active RAS signaling, activation of downstream genes involved in extracellular matrix degradation is absent, whereas loss of SerpinA5 mRNA expression in serous carcinomas was associated with downstream activation of matrix metalloproteinase 9 (MMP9), 16 explaining the invasive potential of serous carcinomas because of degradation of the extracellular matrix.…”
mentioning
confidence: 99%